The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1101/122770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brainwide mapping of endogenous serotonergic transmission via chemogenetic-fMRI

Abstract: Serotonergic transmission affects behaviours and neuro-physiological functions via the orchestrated recruitment of distributed neural systems. It is however unclear whether serotonin's modulatory effect entails a global regulation of brainwide neural activity, or is relayed and encoded by a set of primary functional substrates. Here we combine DREADD-based chemogenetics and mouse fMRI, an approach we term "chemo-fMRI", to causally probe the brainwide substrates modulated by phasic serotonergic activity. We des… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…3) recapitulates similarly contrasting patterns of global activity in cortical and basal forebrain regions observed in humans (Liu et al, 2018), and is consistent with a role of ascending modulatory activity in driving these oscillations (Turchi et al, 2018). The combined use of cell-type specific manipulations and rsfMRI (Giorgi et al, 2017) may permit to probe this mechanistic hypothesis, by enabling causal manipulations of ascending neurotransmitter systems.…”
supporting
confidence: 62%
“…3) recapitulates similarly contrasting patterns of global activity in cortical and basal forebrain regions observed in humans (Liu et al, 2018), and is consistent with a role of ascending modulatory activity in driving these oscillations (Turchi et al, 2018). The combined use of cell-type specific manipulations and rsfMRI (Giorgi et al, 2017) may permit to probe this mechanistic hypothesis, by enabling causal manipulations of ascending neurotransmitter systems.…”
supporting
confidence: 62%
“…Brain slice electrophysiology was carried out as recently described (Giorgi et al, 2017) on young adult 16p11.2 + / + and 16p11.2 + /À mice (12 weeks old, n = 4 per group). Whole-cell patch-clamp recordings were made on pyramidal neurons of the layer V of the prefrontal cortex.…”
Section: Brain Slice Electrophysiologymentioning
confidence: 99%
“…Leveraging the recent implementations of chemo-fMRI in the mouse 21 , we causally probed how cortical silencing affects brain-wide rsfMRI coupling. In contrast to theoretical 10 and experimental 8 evidence predicting that regional inactivation of a neural node would result in reduced functional synchronization with its direct anatomical targets, we found that both chronic and acute silencing of the PFC can counterintuitively increase rsfMRI connectivity within thalamo-cortical substrates of the mouse DMN, encompassing cortical and subcortical regions densely innervated by inactivated medial prefrontal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Here we combine rsfMRI, neural and chemogenetic silencing (chemo-fMRI 21 ) and in vivo electrophysiology in the mouse to probe how inactivation of a cortical area causally affects rsfMRI coupling. Surprisingly, we find that chronic and acute neural silencing of the medial prefrontal cortex (PFC), a core component of the mouse default mode network DMN, 22 may lead to increased rsfMRI coupling between the silenced area and its thalamo-cortical terminals.…”
Section: Introductionmentioning
confidence: 99%